O nascimento de Deus segundo Nietzsche - Faccini, Rafaelo Schmitt (Universidade do Vale do Rio dos Sinos, 2012)
This paper presents the genesis of the concept of God in man, according to the interpretation we make of the philosophy of Friedrich Wilhelm Nietzsche. Through the title "The birth of God according to Nietzsche”, we show how it might arise, according to the philosopher, the belief in the concept of God, interpreting it as a result of a certain hierarchy of forces and will to power to characterize the human species. Addressing the issue of the genesis of the moral idea of God, we realize that Nietzsche does not tell the story of the emergence of a metaphysical entity. What he investigates in works such as "Genealogy of Morals" is, above all, as the concept and feeling of God in man was born and developed in the course of time, always taking into consideration the type of forces and will to power behind this development. To undertake this proposal, we use Nietzsche's own texts, with emphasis on the works and writings of so-called second and third phases of his thought, more accurately, works and writings from "Human, All Too Human," 1878. Included are therefore texts and writings ranging from 1878 to 1889, both appearing in works published during the life of Nietzsche, as in published after his death, among them the issue of "The will to power, "1906, published by Kröner, 1067 with aphorisms. We also made use of some commentators when their positions were relevant to the understanding of these writings.
Keywords: Vontade de poder; Forças; Imanência; Homem; Ideia; Conceito; Crença; Nascimento de Deus; Morte de Deus; Will to power; Forces; Immanence; Human; Idea; Concept; Faith; Birth of God; Death of God; ACCNPQ::Ciências Humanas::Filosofia